Cardioneuroablation: Where are we at? - Pachon, Jose Carlos; Pachon, Enrique Indalecio; Aksu, Tolga; Gopinathannair, Rakesh; Kautzner, Josef; Yao, Yan; Kusumoto, Fred (Heart rhythm O2, 2023)
Since its original description in 2005, catheter ablation techniques, commonly called cardioneuroablation, have emerged as a potential strategy for modulating autonomic function. Multiple investigators have provided observational data on the potential benefits of this technique in a variety of conditions associated with or exacerbated by increased vagal tone such as vasovagal syncope, functional atrioventricular block, and sinus node dysfunction. Patient selection, current techniques including the various mapping strategies, clinical experience, and limitations of cardioablation are reviewed. Finally, while cardioneuroablation has potential to be a treatment option for selected patients with symptoms mediated by hypervagotonia, the document outlines the important knowledge gaps that currently exist and the necessary next steps required before this technique can be widely implemented into clinical practice.
Keywords: Autonomic nervous system; Cardioneuroablation; Cardioneuralablation; Functional bradycardia; Vasovagal syncope